BOOK REVIEW: Roberto Lambertini ed., “Fonti normative francescane: Regola di frate Francesco, Lettere pontificie sulla Regola, Costituzioni narbonensi, Commenti alla Regola”, Padova, EFR-Editrici Francescane, 2016, 568 p., ISBN: 978-88-8135-099-5 - POP, Ioana-Terezia (Studia Universitatis Babeș-Bolyai Historia, 2017)
EFR-Editrici francescane is a consortium that brings together four Italian Franciscan Publishing Houses: Biblioteca Francescana from Milan, Messagero from Padua, Porziuncola from Assisi and Libreria Internazionale Edizioni Francescane from Vicenza. The mission of this consortium since its foundation on 31 March 1995 is, among other things, to promote the Franciscan system of thought and spirituality through publications, conferences or study groups. This collaboration has lead to the publication ofFonti Francescane, Fonti Clariane, Fonti agiografiche or Fonti liturgiche francescane. Fonti normative francescane was published in 2016 and its purpose is to provide the main testimonies that normalize the life of the Order of the Friars Minor to three categories of readers: firstly to a non-specialized public, secondly to researchers interested in the history of the friars minor and thirdly, for the Franciscans themselves. All the texts are, directly or indirectly, concerned with the Rule that norms the life of the Order. Namely, the translations include texts related to the Rule (only two of the three known texts still exist today, respectively the unapproved rule from 1221 and the approved one from 1223) and sources that derive from it: papal documents, the Constitutions of Narbonne and commentaries on the Rule.